Membangun Spirit Tajdid Di Kampus Muhammadiyah: Sinergi Dakwah, Pendidikan, Dan Inovasi - Nur Eva; Ummi Ulfariyani Kadir; St. Nurhayati Ali; Muhammad Nur Maallah (Jurnal Sultra Elementary School, 2026)
The spirit of tajdid (renewal) has been the spirit of the Muhammadiyah movement since its inception, oriented towards the purification of Islamic teachings as well as the dynamism of the people's lives according to the demands of the times. Muhammadiyah campuses as higher education institutions have a strategic role in internalizing the spirit of tajdid through the synergy of da'wah, education, and innovation. This study aims to analyze the concept and implementation of the spirit of tajdid on Muhammadiyah campuses and its relevance in responding to the challenges of globalization, the industrial revolution 4.0, and contemporary socio-religious changes. The method used is a literature study by examining books, journal articles, and official Muhammadiyah documents relevant to the themes of tajdid, Islamic education, and higher education innovation. The results of the study indicate that the spirit of tajdid on Muhammadiyah campuses is manifested in three main pillars: (1) enlightenment da'wah that emphasizes progressive, moderate Islam, and is oriented towards the welfare of the people; (2) education that integrates Islamic, scientific, and Indonesian values ​​holistically; and (3) academic and institutional innovation through the development of research, technology, and social entrepreneurship. The synergy of these three aspects is a crucial foundation for building a superior Muhammadiyah campus that is globally competitive and remains rooted in Islamic values. This study emphasizes that the spirit of renewal is not merely an ideological discourse, but rather a practical paradigm that must be implemented sustainably in all activities of the Tridharma (three pillars) of Muhammadiyah higher education.